Analysis of Students' Financial Behavior in South Tangerang City - Widya Lestari, Ambar; Eliyani, Citra (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This research investigates the influence of financial experience on students’ financial behavior in South Tangerang City, the impact of lifestyle on students’ financial behavior, and the joint effect of both financial experience and lifestyle on financial behavior. A quantitative method using a survey design was applied. The study population consisted of students enrolled at Pamulang University in the 2024/2025 academic year. A purposive sampling technique was used to select 100 participants. Data were collected through observations, interviews, and structured questionnaires. The instruments were first tested for validity and reliability. Additionally, classical assumption tests namely normality, multicollinearity, and heteroscedasticity were performed to meet the prerequisites for multiple linear regression analysis. The findings reveal that both financial experience and lifestyle individually have a statistically significant positive effect on financial behavior. Moreover, the combination of these two variables also contributes significantly to shaping students' financial behavior.